In addition to incision and drainage, are antibiotics indicated for treatment of uncomplicated abscesses?. Issue 10 (October 2015) - Brand, Garth; Colson, Emily
Abstract : Evidence‐Based Answer : Systemic antibiotics are not indicated for treatment of simple abscesses after incision and drainage as there is no improvement in cure rates even in the setting of wounds containing methicillin‐resistant Staphylococcus aureus (MRSA) (SOR: A, meta‐analysis of RCTs). Antibiotics should be considered if systemic inflammatory response syndrome is present (SOR: C, expert opinion).